Aggregation, Distribution and Dynamics in the Linear and Quadratic Expenditure Systems - Buse, Adolf (The Review of Economics and Statistics, 1992)
Using Canadian data (1965-86), the author confirms and extends Thomas M. Stoker's (1986) results on the rule of distributional effects in demand systems. The confirmation consists of evidence from the linear expenditure system model showing that distributional effects are statistically significant and can displace AR(1) dynamics in the disturbances. The extension is made to the quadratic expenditure system model and an argument is advanced that standard habit formation dynamics may reflect omitted distributional effects. The evidence supports this conjecture. This suggests that the author may have been drawing the wrong conclusions from expenditure studies. Rather than inferring dynamic behavior, he should have been concluding that these models are misspecified. Copyright 1992 by MIT Press.